The World's Maritime Axis, A Critical Analysis - Siswoputro, Suspada; Perwita, Anak Agung Banju; Suseto, Budi; Prakoso, Lukman Yudho (Formosa Journal of Science and Technology, 2024)
The dynamics of threats and challenges facing Indonesia in the Southeast Asia and Pacific region continue to develop. Among them is the rivalry between two great powers competing for hegemony over the Asia Pacific accompanied by local and regional threats carried out by non-state actors. This research is an analysis aimed at explaining the basic concept of a strategy introduced by President Jokowi, namely the World Maritime Axis, then testing the extent to which this concept is able to overcome existing threats and challenges, so whether this strategy is worthy of being maintained or not. The research was carried out through literature studies until February 2024. The results show that the World Maritime Axis strategy is worth continuing, and even needs to be supported by the DPR to strengthen its legality in the form of a law.